1989
DOI: 10.1093/carcin/10.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of carcinogen metabolizing enzymes: regulation of the phosphorylation status of the major phenobarbital inducible cytochromes P-450 in hepatocytes

Abstract: We present data showing that the major phenobarbital inducible cytochromes P-450 (cytochrome P-450IIB1 and cytochrome P-450IIB2) were phosphorylated in intact hepatocytes. This phosphorylation was greatly increased by the cAMP derivatives N6-dibutyryl-cAMP and 8-thiomethyl-cAMP mediated by a cAMP-dependent protein kinase. Most importantly the phosphorylation status of cytochromes P-450 was shown to change in the hepatocytes after treatment with glucagon, which is known to increase the level of cAMP in hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The isozyme-specific substrate-dependent protection from phosphorylation and degradation of P450IIE1 in the hepatocytes suggests the mechanism to be of importance for regulation of the specific P450 content in the cell. Definitive proof for a physiological role has to await experiments performed in vivo, although the stabilization mechanism for IIE1 has been reported (6) Previous investigations revealed P4501IB1 to be a target for cAMP-dependent kinase in hepatocytes (18)(19)(20), and phosphorylation of P4501IB1 or IIB4 on Ser-128 (19,21) has been connected to conversion of the protein to the inactive P420 form (22) and to decreased enzymic activity (20). The results herein reported indicate that such phosphorylation is regulated in an isozyme-specific manner by the substrate and might trigger denaturation and heme loss with subsequent apoprotein sorting and degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The isozyme-specific substrate-dependent protection from phosphorylation and degradation of P450IIE1 in the hepatocytes suggests the mechanism to be of importance for regulation of the specific P450 content in the cell. Definitive proof for a physiological role has to await experiments performed in vivo, although the stabilization mechanism for IIE1 has been reported (6) Previous investigations revealed P4501IB1 to be a target for cAMP-dependent kinase in hepatocytes (18)(19)(20), and phosphorylation of P4501IB1 or IIB4 on Ser-128 (19,21) has been connected to conversion of the protein to the inactive P420 form (22) and to decreased enzymic activity (20). The results herein reported indicate that such phosphorylation is regulated in an isozyme-specific manner by the substrate and might trigger denaturation and heme loss with subsequent apoprotein sorting and degradation.…”
Section: Resultsmentioning
confidence: 99%
“…8). Although untreated rat hepatocytes possess low but significant levels of CYP2B1, 28,49,50 in the constitutive situation CYPs other than CYP2B1 or non-CYP enzymes may contribute substantially to the observed effects, potentially further extending the scope of the principle shown in this study. In this context it is interesting that e.g., prostaglandin H synthase (which has recently been found to be expressed in hepatocytes, 51 has been shown to be able to activate CPA.…”
Section: Discussionmentioning
confidence: 73%
“…27 We and others have demonstrated that the major PB inducible CYP2B1 and 2B2 are phosphorylated in intact cells and that this phosphorylation is cAMP-dependent. 28,29 The phosphorylation of CYP2B1 resulted in the downregulation of its activity, 30 showing a novel posttranslational control mechanism for CYP2B1. We have recently shown that cAMP-dependent phosphorylation of CYP2E1 (ethanol-inducible CYP, responsible for activation of many environmental procarcinogens), when tethered to the wildtype phosphoacceptor Ser129, resulted in the reduction of its activity and stabilization of the enzyme protein, whereas substitution of Ser129 by nonphosphorylatable amino acids modified CYP2E1 substrate specificity.…”
mentioning
confidence: 99%
“…In the absence of stimulation, the incorporation of radioactive phosphate into cytochromes P450 (isolated and purified after the incubation.with 32P-orthophosphate) was very low. After stimulation by extracellular glucagon or by membrane permeating cAMP-derivatives (N6,02'-dibutyrylcAMP and 8-thiomethyl cAMP) a marked incorporation of 32P-phosphate into cytochrome P450 took place (15). Autoradiography of gel electrophoretically separated proteins from solubilized microsomes of these hepatocytes and of purified cytochromes P450 combined with visualization on Western blots by specific antibodies showed that four cytochromes P450 were phosphorylated, cytochromes P450 2B1 and2B2, and two cytochromes P450 2B1-related proteins, one of them inducible by phenobarbital (15).…”
Section: Introductionmentioning
confidence: 99%
“…After stimulation by extracellular glucagon or by membrane permeating cAMP-derivatives (N6,02'-dibutyrylcAMP and 8-thiomethyl cAMP) a marked incorporation of 32P-phosphate into cytochrome P450 took place (15). Autoradiography of gel electrophoretically separated proteins from solubilized microsomes of these hepatocytes and of purified cytochromes P450 combined with visualization on Western blots by specific antibodies showed that four cytochromes P450 were phosphorylated, cytochromes P450 2B1 and2B2, and two cytochromes P450 2B1-related proteins, one of them inducible by phenobarbital (15). Pyerin and Taniguchi (16) and Koch and Waxman (17) have also observed that the major phenobarbital-inducible cytochrome P450 is phosphorylated in the intact hepatocytes and in the whole animal (17) where phosphorylation took place in the liver in the absence of any exogenous stimulation and was increased by N6, 02' -dibutyryl-cAMP and theophyllin.…”
Section: Introductionmentioning
confidence: 99%